Race, Performance, Pay and Retention among National Basketball Association Head Coaches - Lawrence M. Kahn (Institute for the Study of Labor (IZA), 2004)
This paper estimates racial differences in the retention probability, pay and performance of NBA coaches over the 1996-2003 period. Using a hazard function approach, I find small and statistically insignificant racial differences in the exit hazard, conditional on team performance, team payroll, and a variety of coaching quality indicators. There were also statistically insignificant racial differences in the quit and discharge hazards, all else equal. Further, among marginal coaches, I find no racial performance differentials, all else equal. Finally, controlling for performance and qualifications, I find small and statistically insignificant racial differences in annual compensation, total contractwide compensation, and contract duration. Together, these findings do not suggest that black NBA coaches are subject to racial discrimination in entry, pay or retention.
Keywords: J44; J63; J15; J71; 330; discrimination; professional sports; managers; Professioneller Sport; Führungskräfte; Lohndifferenzierung; Ethnische Diskriminierung; Schätzung; Vereinigte Staaten; National Basketball Association